2010
DOI: 10.1590/s0100-06832010000500024
|View full text |Cite
|
Sign up to set email alerts
|

Armazenagem de água e produtividade de meloeiro irrigado por gotejamento, com a superfície do solo coberta e desnuda

Abstract: RESUMOEm regiões com escassez hídrica, a irrigação por métodos que otimizam a aplicação de água às plantas torna-se necessária à produção agrícola. Dessa maneira, o conhecimento da armazenagem de água na camada de solo explorada pelas raízes de uma cultura agrícola ao longo de seu desenvolvimento é essencial ao manejo dos recursos água e solo. Partindo desse problema, o objetivo desta pesquisa foi avaliar a armazenagem de água em Cambissolo cultivado com meloeiro, irrigado por gotejamento, sem e com cobertura … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
8

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 26 publications
1
11
0
8
Order By: Relevance
“…MOTTA et al (2010) evaluated the water storage in a Cambisoil cultivated with melon crop; drip irrigated, with and without soil surface cover, and concluded that the soil surface covering increased water storage, especially in initial and vegetative stages of the culture.…”
Section: Resultsmentioning
confidence: 99%
“…MOTTA et al (2010) evaluated the water storage in a Cambisoil cultivated with melon crop; drip irrigated, with and without soil surface cover, and concluded that the soil surface covering increased water storage, especially in initial and vegetative stages of the culture.…”
Section: Resultsmentioning
confidence: 99%
“…The beneficial effect provided by the soil covering, such as reduction in weed infestation (SILVA et al, 2009), reduction of soil temperature (OLIVEIRA et al, 2005), greater nutrient availability (OLIVEIRA et al, 2008), greater microbial biomass (WANG et al, 2008) and greater water economy (OLIVEIRA et al, 2005;MOTA et al, 2010), which promote greater yield in other crops like chives (ARAÚJO NETO et al, 2010) and beets (SEDIYAMA et al, 2011), did not translate into better performance for onion. The use of a protected environment, the residual effect of the succession of organic management in the area and the efficient control of irrigation may have neutralized the effect of the soil coverings.…”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, the culture ranks third in economic importance, with 17.88 t ha -1 average productivity (NUNES et al, 2014;SOUZA;RESENDE, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to point out the homogeneity of the soil in the area (Table 1), which in this case was not an expressive source of variation to affect the results, i.e., the variation in the data for water storage in the 0.0-0.3 m layer was due to the applied treatments, as well as other factors, such as variations in water distribution via irrigation. Details of the discussion on the variation of water storage in the soil of this experiment are presented by Mota et al (2010).…”
Section: Variation Of Soil Water Storage (∆S Z )mentioning
confidence: 99%